Barron's TOEIC practice exams : - Lougheed, Lin (Tổng hợp Thành phố Hồ Chí Minh, 2016)
ESL students preparing to take the Test of English for International Communication will find six full-length practice exams that reflect the actual TOEIC in length, subject matter, question types, and degree of difficulty. Barron's TOEIC Practice Exams manual provides test takers with extensive practice in the actual test-taking experience as an efficient way of improving their score when they take the actual TOEIC. All questions are answered and explained. Audio for the TOEIC tests' listening comprehension section is included on the enclosed audio compact discs.